2017
DOI: 10.1101/100420
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A lineage-related reciprocal inhibition circuitry for sensory-motor action selection

Abstract: The insect central complex and vertebrate basal ganglia are forebrain centres involved in selection and maintenance of behavioural actions. However, little is known about the formation of the underlying circuits, or how they integrate sensory information for motor actions. Here, we show that paired embryonic neuroblasts generate central complex ring neurons that mediate sensory-motor transformation and action selection in Drosophila. Lineage analysis resolves four ring neuron subtypes, R1-R4, that form GABAerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 72 publications
4
28
0
Order By: Relevance
“…To further confine Pros attenuation, we restricted GAL4 activity to the head by employing teashirt (tsh)‐GAL80 (Clyne & Miesenbock, ; Fig EV6) and video‐tracked open‐field behavior of freely moving animals using the Drosophila Arousal Tracking (DART) system (Faville et al , ). While this assay can report differences in motor behavior upon EB circuit perturbations (preprint: Kottler et al ), analysis of controls and animals with supernumerary R neurons revealed no significant differences (Fig A–D). Together with the observed functional anatomy (Fig ), these data suggest that Pros‐attenuated, supernumerary GABAergic interneurons are physiologically active and integrate into ellipsoid body R neuron circuitry without detriment to sensory‐motor integration and higher motor control.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…To further confine Pros attenuation, we restricted GAL4 activity to the head by employing teashirt (tsh)‐GAL80 (Clyne & Miesenbock, ; Fig EV6) and video‐tracked open‐field behavior of freely moving animals using the Drosophila Arousal Tracking (DART) system (Faville et al , ). While this assay can report differences in motor behavior upon EB circuit perturbations (preprint: Kottler et al ), analysis of controls and animals with supernumerary R neurons revealed no significant differences (Fig A–D). Together with the observed functional anatomy (Fig ), these data suggest that Pros‐attenuated, supernumerary GABAergic interneurons are physiologically active and integrate into ellipsoid body R neuron circuitry without detriment to sensory‐motor integration and higher motor control.…”
Section: Resultsmentioning
confidence: 93%
“…Temporal patterning of progenitors defines the identity of their neuronal progeny. We therefore predicted that supernumerary DAL NSCs should generate supernumerary Poxn and GABA‐expressing ellipsoid body R neurons (preprint: Kottler et al ), which upon differentiation would be able to project into the ellipsoid body ring neuropil.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the strength of connectivity can be modulated by dopamine-related learning processes (Waddell, 2013 ), so that the EB effectively integrates current and previous information about all its incoming sensory inputs. In turn, the EB processes its incoming input to release the inhibition of appropriate premotor programs in the LAL, selecting actions in response to the computed sensory stimuli (Fiore et al, 2015 ; Kottler et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%